The “Necessity” of Democracy for Sustainable Development: A Comparison between the USA and Cuba - Rand, Marcus (Consilience, 2014)
Democracy is associated with, and often stated as a condition for, sustainable development. A comparison of Cuba and the United States shows that sustainable development can exist and grow in countries that do not possess a democratic form of governance. The results of the comparison indicate that, to promote sustainable development on a wider scale, it is necessary to focus on the values embedded in the dignity of humankind. To promote such values, it is imperative to present sustainable development as a set of values linked to the rights and dignity of humankind, not as the sole offspring of democratic ideology.